(untitled) (Journal of Philosophy Culture and Political Science, 2021)
The article covers sports diplomacy of the Post-Soviet states. Sports diplomacy is viewed as a foreign policy tool to form an attractive image of the country by holding and participating in international sports events, sending representatives of the country to international sports federations and specialized agencies. Authors offer various dimensions of the sports diplomacy of the Post-Soviet states – from hosting Olympic games and world championships to promoting national sports. They also conduct analysis of the Post-Soviet sports diplomacy. In the conclusion they offer steps that could have been implemented to foster cooperation in this sphere.